Risk of Juvenile Idiopathic Arthritis and Rheumatoid Arthritis in Patients With Celiac Disease: A Population-Based Cohort Study. (16th December 2022) - Doyle, John B.; Lebwohl, Benjamin; Askling, Johan; Forss, Anders; Green, Peter H.R.; Roelstraete, Bjorn; Söderling, Jonas; Ludvigsson, Jonas F.
Abstract : INTRODUCTION: Celiac disease (CD) is associated with many immune-mediated conditions, but a definitive epidemiological association between CD and juvenile idiopathic arthritis (JIA) or rheumatoid arthritis (RA) has not been established. We quantified the risk of JIA and RA among patients with CD using a population-based cohort. METHODS: We identified patients diagnosed with biopsy-proven CD between 2004 and 2017 using data from a national histopathology cohort in Sweden. Each patient was matched by age, sex, calendar year, and geographic region to reference individuals in the general population. We calculated the incidence and estimated the relative risk, through Cox proportional hazards models, of JIA in individuals with CD aged <18 and of RA in individuals with CD aged ≥18. RESULTS: We identified 24, 014 individuals with CD who were matched to 117, 397 reference individuals from the general population. Among individuals aged <18, the incidence rate of JIA was 5.9 per 10, 000 person-years in patients with CD and 2.2 per 10, 000 person-years in the general population (n events = 40 and 73, respectively; hazard ratio [HR] 2.68, 95% confidence interval 1.82–3.95) over a follow-up of 7.0 years. Among individuals aged ≥ 18, the incidence of RA was 8.4 per 10, 000 person-years in CD and 5.1 per 10, 000 person-years in matched comparators (n events = 110 and 322, respectively; HR 1.70, 95% confidence interval 1.36–2.12) over a follow-up of 8.8 years. DISCUSSION: Among children with CD, JIA develops nearly 3 times as often as it does in the general population, and among adults with CD, RA occurs nearly 2 times as often. Clinicians caring for patients with CD with joint symptoms should have a low threshold to evaluate for JIA or RA.